Modified National Early Warning Scores (MNEWS) for Predicting the Outcomes of Suspected Sepsis Patients; A Prospective Cohort Study - Nipon Diskumpon; Busabong Ularnkul; Winchana Srivilaithon; Pariwat Phungoen; Kiattichai Daorattanachai (Archives of Academic Emergency Medicine)
Introduction: The National Early Warning Score (NEWS) is commonly used to identify patients at high mortality risk. However, it has notable limitations. In this study, to enhance the accuracy, we revised it and evaluated the performance of modified NEWS (MNEWS) in predicting the outcomes of suspected sepsis patients.